PERMASALAHAN PUTUS SEKOLAH PENDIDIKAN DASAR - Rizki Ananda; Yosi Anggraini; Suci Rahmadani; Nadiah Lestiwi Ramadani; Arzila Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem of dropping out of school at the elementary education level in Indonesia is still a crucial issue that hinders the achievement of nine-year compulsory education. The latest data shows that tens of thousands of elementary school-aged children do not continue their education, mainly due to family economic factors, limited access to education, and social and cultural influences. Government efforts to reduce the dropout rate include strengthening non-formal education, empowering local communities, and volunteer teaching programs. Dropping out of school at the elementary education level is a serious problem still faced by Riau Province. Based on data from the Riau Provincial Education Office, around 44.37% of school-aged children drop out of school, making Riau the third highest in Indonesia. The main causal factors include family economic limitations, difficult-to-reach geographical conditions, low public awareness of the importance of education, and lack of facilities and government support. This study aims to identify the factors causing dropouts in elementary education in Riau and evaluate local government efforts to overcome these problems. The methods used are literature studies and secondary data analysis from various official sources and current news. The results of the study show that economic and geographical factors are the main obstacles, while government support still needs to be strengthened in order to significantly reduce the dropout rate. This article recommends increasing social assistance programs, improving access to education in remote areas, and increasing socialization of the importance of education to the community.